Improving the photostabilization of poly(vinyl chloride) using 4-(benzylideneamino) benzenesulfonamide tin complex / Hassan Ghani ...[et al.] - Ghani, Hassan; Yousif, Emad; Kadhom, Mohammed; Abdo Ahmed, Waled; Yusop, Muhammad Rahimi; Bufaroosha, Muna (Universiti Teknologi MARA, 2022)
The photostabilization of poly (vinyl chloride) (PVC) film filled with an organotin complex in its structure was examined and compared with the blank PVC film. The organotin (IV) complex that contains 4-(benzylideneamino) benzenesulfonamide as a ligand was synthesized and applied as a PVC photostabilizer. The impact of the complex on the polymer was assessed by comparing the properties of the films with and without the complex, before and after irradiation, using Fourier transform infrared spectroscopy, weight loss, viscosity change, atomic force microscopy, and field emission scanning electron microscopy (FE-SEM). Results showed that the complex film had lower weight loss, gel content, and molecular weight deterioration than the plain PVC film. Also, surfaces of the complexes-filled films were smoother, less lumpy, and more homogeneous. These findings were obtained via the FE-SEM and light microscope images and confirmed by measuring the roughness factor. The organotin (IV) complex proved its activity in delaying the photo-degradation of PVC by several mechanisms. Ultimately, the Tin complex has effectively protected the PVC film against irradiation.